Research Progress on Embryonic Development, Genetic Regulation and Clinical Management of Congenital Middle Ear Malformations - Gao, Xiaochen; Li, Chengzhilin; Yuan, Fanyu; Cao, Xue; Liu, Chengcheng; Qi, Wenwen; Xie, Fengyang; Xia, Ming (Flavour and fragrance journal, 2025)
Congenital middle ear malformations are a common hearing defect in newborns, primarily characterised by abnormal middle ear structures, particularly underdeveloped or malformed ossicular chains, resulting in conductive hearing loss. This article provides a comprehensive review of the embryonic development process of the middle ear and the genetic regulatory mechanisms, with a focus on the Tbx1 gene, which is closely related to middle ear development. Studies have shown that the Tbx1 gene plays a crucial role in the migration of neural crest cells and the formation of middle ear structures, and its mutation or abnormal expression can lead to developmental defects of the middle ear structure. These gene mutations affect downstream signalling pathways (such as FGF8 , FGF10 and BMP4 ), which are essential in the formation of the ossicles, ear canal and middle ear cavity. Additionally, this article discusses the aetiology of congenital middle ear malformations, associated syndromes, clinical manifestations, classification, diagnosis and treatment strategies. Diagnostic methods for middle ear malformations include audiological examinations, imaging studies and genetic testing. Early diagnosis and intervention, such as surgical correction and the use of hearing aids, can help improve the hearing and quality of life of patients. This article aims to provide a reference and basis for further etiological research and precise treatment by elucidating the mechanisms and clinical features of middle ear malformations.